IMPLEMENTASI METODE CONCEPT MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SAINS DAN KREATIVITAS SISWA KELAS VI SDN BENER 01 TAHUN PELAJARAN 2017/2018 - Sudjinah Sudjinah (UNIVERSITAS PGRI MADIUN, 2018)
The science lesson at SDN Bener 01 shows that learning is still teacher-centered. Student creativity is not yet optimal. Learning completeness with KKM 75 only reached 35% and students still tend to passive. Therefore it is necessary to improve the learning process. The purpose of this research is to find out whether the application of concept mapping method can improve the learning outcomes of science and creativity of students of class VI SDN Bener 01 in the 2017/2018 school year. Concept Mapping is a learning strategy that asks students to synthesize or draw a picture of the main concepts that are interconnected, which are marked by lines of arrows written levels that sound the form of relationships between the main concepts. This research is a Class Action Research conducted at SDN Bener 01 as much as two cycle consist of cycle I and cycle II. Technique of collecting data using test and observation sheet of student creativity. The result of this class action research is on the first cycle student learning outcomes show mastery learning classically 59%. While the creativity of students showed 65% of students with creative criteria and 35% with creative enough criteria. The learning outcomes in cycle II showed that learning completeness in the classical reach 82%. While the creativity of students showed 29% of students with very creative category, 65% category creative enough and 6% creative enough. Increased learning outcomes from cycle I to cycle II as much as 23%. Enhancement of creativity of students as much as 29%. The conclusion of this PTK is the application of concept mapping method can improve science learning outcomes and creativity of students of class VI SDN Bener 01 Year lesson 2017/2018.